PROSTAGLANDINS ANALOGUES DURING CATARACT PHACOEMULSIFICATION ON THE BACKGROUND OF PRIMARY GLAUCOMA - I. E. Ioshin (Scientific Сentre for Family Health and Human Reproduction Problems, 2016)
We analysed the effect of prostoglandins analogues application on the course of postoperative period of cataract phakoemulsification in 58 patients with primary open-angle glaucoma. All patients before the operation had normal intraocular pressure (on average 15.6 ± 0.07 mm Hg), the optical coherent tomography showed normal parameters of retina thickness in 1 mm zone and the macula volume in 6 mm zone. Instillation of nonsteroid anti-inflammatory drug after the operation lasted 6-8 weeks, and prostoglandins analogues continued to be instillated during all period of observation. The course of the early postoperative period was areactive. Average visual acuity on the first day was 0.69 ± 0.05, in 6-8 weeks - 0.85 ± 0.05. The average level of intaocular pressure during application of prostoglandins analogues on first day was 16.9 ± 0.37 mm Hg, and in 6-8 weeks -15.1 ± 0.28 mm Hg. Optical coherence tomography revealed little change of retina thickness and macular area volume before the operation and in 6-8 weeks after it was regarded as an error of measurement method. Thus, continuation of instillations of prostoglandins analogues in pre- and postoperative period in uncomplicated phakoemulsification in patients with primary open-angle glaucoma promote continuity in treatment, support com-plience and provide stable intraocular pressure without the expressed reactive hypertensia. Application of nonsteroid anti-inflammatory drug during 6-8 weeks after phakoemulsification in patients with primary open-angle glaucoma serves as an effective measure of prevention of inflammation of an anterior and posterior eye segment during prostoglandins analogues treatrment.